2017
DOI: 10.1155/2017/1537538
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant System Response and cDNA-SCoT Marker Profiling inPhoenix dactyliferaL. Plant under Salinity Stress

Abstract: Many Phoenix dactylifera (date palm) cultivars are grown in the arid and semiarid regions of the world, including Saudi Arabia. P. dactylifera is highly tolerant to salinity stress. To investigate the response of Khalas cultivar of P. dactylifera, two-month-old plants were treated with sodium chloride (50, 100, and 150 mM NaCl) for three months. Our result showed that proline content was higher in all treated plants compared to control plants. Thiobarbituric acid reactive substances (TBARS) were increased at 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 68 publications
2
1
0
Order By: Relevance
“…treated with a wide range of NaCl solutions. The gradual increase in CAT activity after 28 d during NaCl-induced stress recorded in the present study is similar to the phenomenon reported before in date palm ( Phoenix dactylifera L.) (Al-Qurainy et al, 2017). It is noteworthy that CaCl 2 triggered only slight CAT changes in silver maple tissues, which may indicate its lower phytotoxicity.…”
Section: Discussionsupporting
confidence: 92%
“…treated with a wide range of NaCl solutions. The gradual increase in CAT activity after 28 d during NaCl-induced stress recorded in the present study is similar to the phenomenon reported before in date palm ( Phoenix dactylifera L.) (Al-Qurainy et al, 2017). It is noteworthy that CaCl 2 triggered only slight CAT changes in silver maple tissues, which may indicate its lower phytotoxicity.…”
Section: Discussionsupporting
confidence: 92%
“…This agrees with Abdel-Lateif and Hewedy [49], who found that the P5CS gene expression patterns and SCoT patterns were different among eight cultivars of Egyptian wheat. Also, agrees with Al-Qurainy et al [50], who reported that cDNA-SCoT marker in date palm showed a variation in different gene expressions profiling between treated and untreated plants under various NaCl concentrations. This indicates the SCoT markers may be co-localized with P5CS gene which is increasingly expressed under water deficit [23].…”
Section: P5cs Gene Relative Expressionsupporting
confidence: 91%
“…While it appears that excessive concentration of ROS damages the plant, low levels are part of signaling mechanisms that acclimate to biotic and abiotic stresses [11][12][13]. Experts seriously rely on the enhancement of the plant stress defense system as the real key to providing agriculture with productivity and quality of food, energy, fiber and raw materials [14][15][16][17][18][19]. Scientific studies on the effects of stressful factors on the physiological, histological and developmental behavior of crop plants report ascorbic acid, polyethylene glycol and herbicides are organic and inorganic substances, highly effective in making plant stress defense system healthier and extremely reactive to free radicals [20][21][22].…”
Section: Introductionmentioning
confidence: 99%